Ethical AI Practices in E-Commerce Companies: Evidence from Henan Toward, China Toward a Policy Guide - Shangyuan, Du; Ricafort, Reagan (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the ethical artificial intelligence practices of selected e-commerce companies operating in Henan Province, China and developed a basis for a region-specific policy guide for responsible AI governance. It was anchored on the Fairness, Accountability, and Transparency Framework and the Privacy by Design Framework, which guided the assessment of fairness, accountability, transparency, and privacy in AI-driven e-commerce systems. The study used a mixed-methods descriptive design that combined a structured 4-point Likert-scale survey questionnaire and semi-structured interviews. The respondents were employees engaged in AI-related or data-driven operations and selected management-level personnel from Alibaba, JD.com, Meituan, and Pinduoduo with operational presence in Henan Province. Quantitative data were analyzed using percentage, weighted mean, standard deviation, and ANOVA, while qualitative data were treated through thematic analysis. The findings showed that respondents generally perceived ethical AI practices at an agreeable level across fairness (2.72), accountability (2.84), transparency (2.85), and privacy (2.82). No significant differences were found when respondents were grouped according to company and years in service. However, fairness significantly differed by educational attainment, while privacy significantly differed by frequency of AI interaction. The challenges in implementing AI technologies were rated serious overall (2.93), with the most critical issue involving the misuse of AI by fraudsters through fake images, fake reviews, and fraudulent refund claims. Other major concerns included regulatory compliance, customer misunderstanding of AI decisions, cybersecurity risks, technical integration difficulties, and continuous investment demands. The study concluded that ethical AI practices were present but still required stronger and more consistent governance. It recommended the development and application of a region-specific policy guide aligned with the PIPL and DSL to improve fairness, accountability, transparency, privacy, and organizational compliance. The study is relevant to SDG 8, SDG 9, and SDG 16 because it addresses responsible innovation, sustainable digital commerce, and stronger institutional governance. Its sustainability impact lies in supporting technological, socio-economic, policy, community, and institutional sustainability through more ethical and human-centered AI implementation in e-commerce.
Keywords: Accountability; E-commerce; Ethical AI Practices; Fairness; Henan Province; Privacy; Transparency